a) 3x+2+3x = 10
b) (2x - 3)3=125
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: -2x(x+3)+x(2x-1)=10
=>-2x^2-6x+2x^2-x=10
=>-7x=10
=>x=-10/7
b: Sửa đề: 2/3x(9/2x+1/4)-(3x^2+2)=3
=>3x^2+1/6x-3x^2-2=3
=>1/6x-2=3
=>x=30
A = - 3\(x\).(\(x-5\)) + 3(\(x^2\) - 4\(x\)) - 3\(x\) - 10
A = - 3\(x^2\) + 15\(x\) + 3\(x^2\) - 12\(x\) - 3\(x\) - 10
A = (- 3\(x^2\) + 3\(x^2\)) + (15\(x\) - 12\(x\) - 3\(x\)) - 10
A = 0 + (3\(x-3x\)) - 10
A = 0 - 10
A = - 10
a: Ta có: \(5\left(4x-1\right)+2\left(1-3x\right)-6\left(x+5\right)=10\)
\(\Leftrightarrow20x-5+2-6x-6x-30=10\)
\(\Leftrightarrow8x=43\)
hay \(x=\dfrac{43}{8}\)
b: ta có: \(2x\left(x+1\right)+3\left(x-1\right)\left(x+1\right)-5x\left(x+1\right)+6x^2=0\)
\(\Leftrightarrow2x^2+2x+3x^2-3-5x^2-5x+6x^2=0\)
\(\Leftrightarrow6x^2-3x-3=0\)
\(\Leftrightarrow2x^2-x-1=0\)
\(\Leftrightarrow\left(x-1\right)\left(2x+1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=1\\x=-\dfrac{1}{2}\end{matrix}\right.\)
a) 2x+10=0->2x=-10->x=-5
b) 4(x-1)+3x-5=0->4x-4+3x-5=0
=7x-9=0->7x=-9->x=-1.28571428571
c)-1 1/3x^2+x=0
=-3x^2/-3x^2+x=0
=1+x=0
x=-1
c: =>-4/3x^2+x=0
=>x(-4/3x+1)=0
=>x=0 hoặc x=3/4
a: 2x+10=0
=>2x=-10
=>x=-5
b: =>4x-4+3x-5=0
=>7x-9=0
=>x=9/7
`#040911`
`a)`
\(\left(2x-1\right)^2-\left(2x+5\right)\left(2x+1\right)=10\)
\(\Leftrightarrow 4x^2 - 4x + 1 - (4x^2 + 12x + 5) = 10 \\ \Leftrightarrow 4x^2 - 4x + 1 - 4x^2 - 12x - 5 = 10 \\ \Leftrightarrow (4x^2 - 4x^2) - (4x + 12x) + (1 - 5) = 10 \\ \Leftrightarrow -16x - 4 = 10 \Leftrightarrow -16x = 10 + 4 \\ \Leftrightarrow -16x = 14 \\ \Leftrightarrow x = \dfrac{-7}{8}\)
Vậy, `x = -7/8`
`b)`
`9^2(x - 1) + 25(1 - x) = 0`
`<=> 9^2(x - 1) - 25(x - 1) = 0`
`<=> (x - 1)(9^2 - 5^2) = 0`
`<=>`\(\left[{}\begin{matrix}x-1=0\\9^2-5^2=0\end{matrix}\right.\)
`<=>`\(\left[{}\begin{matrix}x=1\\56=0\left(\text{vô lý}\right)\end{matrix}\right.\)
Vậy, `x = 1`
`c)`
`x^2+3x - 4 = 0`
`<=> x^2 + 4x - x - 4 = 0`
`<=> (x^2 - x) + (4x - 4) = 0`
`<=> x(x - 1) + 4(x - 1) = 0`
`<=> (x + 4)(x - 1) = 0`
\(\Leftrightarrow\left[{}\begin{matrix}x+4=0\\x-1=0\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=-4\\x=1\end{matrix}\right.\\ \text{Vậy, }x\in\left\{-4;1\right\}\)
a: =>4x^2-4x+1-(4x^2+2x+10x+5)=10
=>4x^2-4x+1-10-4x^2-12x-5=0
=>-16x-4=0
=>x=-1/4
b: =>(x-1)(9^2-25)=0
=>x-1=0
=>x=1
c: =>x^2+4x-x-4=0
=>(x+4)(x-1)=0
=>x=1 hoặc x=-4
a) \(\left(2x-1\right)^5=243\)
\(\left(2x-1\right)^5=3^5\)
\(\Rightarrow2x-1=3\)
\(2x=3+1\)
\(2x=4\)
\(x=\frac{4}{2}\)
\(x=2\)
Vậy .......
b) \(\left(3x+2\right)^3=125\)
\(\left(3x+2\right)^3=5^3\)
\(\Rightarrow3x+2=5\)
\(3x=5-2\)
\(3x=3\)
\(x=\frac{3}{3}=1\)
Vậy ..........
a) \(\left(x+1\right)^3-\left(x-1\right)^3-6\cdot\left(x-1\right)^2=10\)
\(\Rightarrow x^3+3x^2+3x+1-x^3+3x^2-3x+1-6\cdot\left(x^2-2x+1\right)=10\)
\(\Rightarrow6x^2+2-6x^2+12x-6=10\)
\(\Rightarrow12x-4=10\)
\(\Rightarrow12x=14\)
\(\Rightarrow x=\dfrac{7}{6}\)
b) \(x\left(x+5\right)\left(x-5\right)-\left(x+2\right)\left(x^2-2x+4\right)=42\)
\(\Rightarrow x\left(x^2-25\right)-\left(x^3+8\right)=42\)
\(\Rightarrow x^3-25x-x^3-8=42\)
\(\Rightarrow-25x-8=42\)
\(\Rightarrow-25x=50\)
\(\Rightarrow x=\dfrac{50}{-25}=-2\)
c) \(\left(x-2\right)^3-\left(x-3\right)\left(x^2+3x+9\right)+6\left(x+1\right)^2=49\)
\(\Rightarrow x^3-6x^2+12x-8-\left(x^3-27\right)+6\left(x^2+2x+1\right)=49\)
\(\Rightarrow x^3-6x^2+12x-8-x^3+27+6x^2+12x+6=49\)
\(\Rightarrow24x+25=49\)
\(\Rightarrow24x=24\)
\(\Rightarrow x=\dfrac{24}{24}=1\)
\(3^x.\left(3^2+1\right)=10\)
\(3^x.10=10\)
\(3^x=\frac{10}{10}=1\)
\(x=0\)
a) 3x+2 + 3x = 10
3x.(32 +1) = 10
3x.10 = 10
3x = 1 = 30
=> x =0
b) (2x-3)3 = 125 = 53
=> 2x - 3 = 5
2x = 8
x = 4